Reduced Lung Function at Preschool Age in Survivors of Very Low Birth Weight Preterm Infants - Chang, Hung-Yang; Chang, Jui-Hsing; Chi, Hsin; Hsu, Chyong-Hsin; Lin, Chia-Ying; Jim, Wai-Tim; Peng, Chun-Chih (Frontiers in Pediatrics, 2020)
Background: Survivors of preterm birth are at risk of long-term respiratory consequences. The objective of this prospective study was to assess pulmonary function at preschool age of former very low birth weight (VLBW) preterm children. Methods: Lung function of children born preterm and term controls aged 5–6 years were assessed by spirometry. The results were converted to z-scores. A questionnaire regarding respiratory symptoms was completed. Associations to gestational age (GA), birth weight (BW), bronchopulmonary dysplasia (BPD), and perinatal factors were assessed. Results: In total, 85 VLBW preterm children and 29 term controls were studied. Of the preterm children, the mean GA was 28.6 ± 2.6 weeks and the mean BW was 1,047 ± 273 gm. Preterm children had significantly lower z-scores of forced expiratory volume in 1 s (FEV1), FEV1/forced vital capacity (FVC) ratio, and forced expiratory flow rate between 25–75% of FVC (FEF25−75), compared with term controls (−0.73 vs. 0.04, p = 0.002; −0.22 vs. 0.39, p = 0.003; −0.93 vs. 0.0, p < 0.001; respectively). Further segregation of the preterm group revealed significantly impaired FEV1, FEF25−75 in children at earlier gestation (≤ 28 weeks, n = 45), lighter at birth (≤ 1,000 g, n = 38), or with BPD (n = 55) compared with term controls (p < 0.05). There were significant negative relationships between the severity of BPD with FEV1, FVC, and FEF25−75 (p < 0.05). However, no correlation between lung function measurements and respiratory symptoms was found. Conclusions: VLBW preterm infants have reduced lung function at preschool age, especially among those with younger GA, lower BW, and BPD. Additional long-term follow-up of respiratory outcomes are needed for this vulnerable population.